2019
DOI: 10.1007/s12017-019-08532-y
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment with microRNA-181a Antagomir Prevents Loss of Parvalbumin Expression and Preserves Novel Object Recognition Following Mild Traumatic Brain Injury

Abstract: Mild traumatic brain injury (mTBI) can result in permanent impairment in memory and learning and may be a precursor to other neurological sequelae. Clinical treatments to ameliorate the effects of mTBI are lacking. Inhibition of microRNA-181a (miR-181a) is protective in several models of cerebral injury, but its role in mTBI has not been investigated. In the present study, miR-181a-5p antagomir was injected intracerebroventricularly 24 h prior to closed-skull cortical impact in young adult male mice. Paw withd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 64 publications
(75 reference statements)
1
16
0
Order By: Relevance
“…Parvalbumin-immunoreactive (PV-IR) interneurons comprise a large proportion of inhibitory GABAergic interneurons in the hippocampus (and amygdala), and are intricately involved in the neuronal circuitry required for FC acquisition, storage and retrieval [4447]. Loss of PV-IR cells in the dentate gyrus, as observed here, has been reported previously in male rodents following LFP [48, 49] or concussive brain injury [50]. The loss of these inhibitory interneurons has been associated with increased dentate gyrus excitability [48] and a chronic, progressive loss of synaptic inhibition [49].…”
Section: Discussionsupporting
confidence: 69%
“…Parvalbumin-immunoreactive (PV-IR) interneurons comprise a large proportion of inhibitory GABAergic interneurons in the hippocampus (and amygdala), and are intricately involved in the neuronal circuitry required for FC acquisition, storage and retrieval [4447]. Loss of PV-IR cells in the dentate gyrus, as observed here, has been reported previously in male rodents following LFP [48, 49] or concussive brain injury [50]. The loss of these inhibitory interneurons has been associated with increased dentate gyrus excitability [48] and a chronic, progressive loss of synaptic inhibition [49].…”
Section: Discussionsupporting
confidence: 69%
“…Various results indicate that miR-181a-5p plays an important role in ISO-induced cognitive impairment. Some research suggested that overexpression of miR-181a has been shown to contribute to brain nerve damage, including Parkinson’s disease and epilepsy [26, 27], and has been associated with behavioral changes following nerve damage in rodents [28]. Therefore, we hypothesized that overexpression of miR-181a-5p promoted the occurrence and progression of cognitive impairment and neuroinflammation in ISO-exposed rats.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we hypothesized that overexpression of miR-181a-5p promoted the occurrence and progression of cognitive impairment and neuroinflammation in ISO-exposed rats. Mild traumatic brain injury can cause permanent damage to learning and memory ability, and Griffiths et al [28] found that inhibition of miR-181a expression could have a protective effect on brain injury in mice after injecting miR-181a inhibitor into mice with mild brain injury. This study also supports our conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Also of particular interest was no change in PV-expressing cell density in the AMY and the HP, as PV-IR cells in these regions have been demonstrated to be important for memory consolidation. 54,56 PV-IR cell density in the dentate gyrus of the HP has been previously reported to decrease following experimental TBI, 39,58,61,62 and this cell loss has been associated with impaired performance on contextual and cued DFC test performance following repetitive concussive brain injuries in male mice. 39 But, another pathological mechanism must account for impaired TFC performance following repeated CHIMERA injuries, as well as for the observed MWM deficits.…”
Section: Summary Of Pathological Findingsmentioning
confidence: 89%
“…Main effect of injury, CHIMERA < Sham Main effect of sex, Male < Female TFC-cue test, total freezing during trace periods (Fig. 9D) COGNITIVE DYSFUNCTION FOLLOWING CHIMERA focal concussive 39,58 or lateral fluid percussion injury, [59][60][61][62] which results in a mixed focal-diffuse injury. In addition, CCI resulted in a reduction in PV-expressing interneurons in both the HP and AMY.…”
Section: Summary Of Pathological Findingsmentioning
confidence: 99%